Hierarchial Zeolites: Beyond Creation of Mesoporosity: The Advantages of Polymer‐Based Dual‐Function Templates for Fabricating Hierarchical Zeolites (Adv. Funct. Mater. 12/2016). (March 2016) - Tian, Qiwei; Liu, Zhaohui; Zhu, Yihan; Dong, Xinglong; Saih, Youssef; Basset, Jean‐Marie; Sun, Miao; Xu, Wei; Zhu, Liangkui; Zhang, Daliang; Huang, Jianfeng; Meng, Xiangju; et al.
Abstract : A new synthetic strategy is developed for fabricating hierarchically structured zeolite materials, which features the use of cationic non‐surfactant polymers as dual‐functional templates. Y. Han and co‐workers show, on page 1881, that the mutual interpenetration of the polymer and the zeolite networks renders disordered but highly interconnected mesopores in zeolite crystals. This strategy also enables the synthesis of unprecedented core‐shell‐structured hierarchical zeolites.